2020
DOI: 10.1108/jed-02-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Investors’ attention: does it impact the Nigerian stock market activities?

Abstract: PurposeThe author investigates whether investors’ online information demand measured by Google search query and the changes in the numbers of Wikipedia page view can explain and predict stock return, trading volume and volatility dynamics of companies listed on the Nigerian Stock Exchange.Design/methodology/approachThe multiple regression model which encompasses both the univariate and multivariate regression framework was employed as the research methodology. As part of our pre-analysis, we test for multicoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
1
0
3
Order By: Relevance
“…Sự chú ý của nhà đầu tư được rất nhiều nghiên cứu lượng hóa bằng chỉ số Google Trend. Các nghiên cứu theo hướng này cho các thị trường đang phát triển có thể kể đến như: Công trình của Nguyen và cộng sự (2020), Irabor (2021), và Nguyen và cộng sự (2019). Tuy nhiên, kết quả thu được vẫn còn nhiều tranh cãi.…”
Section: Mô Hình Nghiên Cứuunclassified
See 1 more Smart Citation
“…Sự chú ý của nhà đầu tư được rất nhiều nghiên cứu lượng hóa bằng chỉ số Google Trend. Các nghiên cứu theo hướng này cho các thị trường đang phát triển có thể kể đến như: Công trình của Nguyen và cộng sự (2020), Irabor (2021), và Nguyen và cộng sự (2019). Tuy nhiên, kết quả thu được vẫn còn nhiều tranh cãi.…”
Section: Mô Hình Nghiên Cứuunclassified
“…Trong khi Nguyen và cộng sự (2020) cho rằng mức độ chú ý có tương quan dương với tỷ suất sinh lời và lượng giao dịch của cổ phiếu, thì Nguyen và cộng sự (2019) khẳng định kết quả ngược lại. Sử dụng dữ liệu của thị trường Nigeria, Irabor (2021) kết luận không có mối tương quan nào giữa tần suất tìm kiếm trên Google với tỷ suất sinh lời của thị trường. Như vậy, mối quan hệ giữa sự chú ý của nhà đầu tư với biến động của thị trường chứng khoán ở các nước đang phát triển vẫn cần được kiểm chứng nhiều hơn.…”
Section: Mô Hình Nghiên Cứuunclassified
“…However, while C. Nguyen et al (2020) concluded a positive relationship between these two variables, C. P. Nguyen et al (2019) proved the relationship in the opposite direction. Another study by Osarumwense (2020) shows that investor attention does not impact stock returns in the Nigerian market. Therefore, more research should be conducted for frontier markets to provide further evidence about the relationship between search intensity and stock prices and to point out the reasons for different study results.…”
Section: Introductionmentioning
confidence: 97%
“…Yatırımcı ilgisinin doğrudan temsilcisi olarak kullanılan bu araçlar temelde yatırımcıların bilgiyi elde etmek için harcadıkları çabaya yani bilgi arama davranışlarına ilişkin veriler sunmaktadır. Yatırımcıların bilgi arayışlarına dayanan ve yatırımcı ilgisinin doğrudan temsilcisi olarak kabul edilen bu araçlar arasında Google (Da ve diğerleri, 2011;Colaco ve diğerleri, 2017;Padungsaksawasdi ve diğerleri, 2019) ve Baidu (Zhang ve diğerleri, 2013;Zhang, 2019;Zhao ve diğerleri, 2018;Nguyen ve diğerleri, 2019) arama hacimleri, Wikipedia sayfalarının görüntülenme sayısı (Boulton ve diğerleri, 2021;Osabuohien-Irabor, 2021, Gómez-Martínez ve diğerleri, 2022 ve tweetler (Li ve diğerleri, 2016;Shen ve diğerleri, 2019;Rakowski ve diğerleri, 2021;Suardi ve diğerleri, 2022) sayılabilir.…”
Section: Introductionunclassified